Ks. Przemysław Artemiuk, "Kim jest papież w Kościele. Szkice z teologii prymatu", Płocki Instytut Wydawniczy, Płock 2022, ss. 256 - Głowacki, Paweł (Vox Patrum, 2026)
Review of the book: Ks. Przemysław Artemiuk, "Kim jest papież w Kościele. Szkice z teologii prymatu", Płocki Instytut Wydawniczy, Płock 2022.